Corporate Social Responsibility (CSR), Organisational Support and Employee Engagement:Case Study Approach - Olawale O. Olabode; Felix Chidozie (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2022)
Corporate social responsibility is how committed an organisation is in order to contribute to sustainable economic development by working with all stakeholders to improve quality of life. Today, every society expects a lot from companies to be socially responsible of providing developmental services to the community it operates (i.e., in local palace, ‘giving back to the society’). Many organisations are not practicing it and unwittingly toying with their reputation and probably their bottom line (social, environmental and economic performance). In lieu of this, this study assesses Corporate Social Responsibility (CSR), organisational support and employee engagement: Adopting Department of Petroleum Resources (DPR), Akure as case study. This study uses primary sources of data through a questionnaire. Twenty-five (25) questionnaire is administered to employees of DPR Akure through a purposive sampling method. However, only 11 questionnaire is correctly filled and returned, which represents 44% response rate, while remaining 14 represents 56%. This low percentage recorded reveals that DPR Akure is an annex of the corporation with few number of employees. Both descriptive statistics (tables, frequencies, percentages) and one-sample ‘t’ test for means statistics are used to analyse the collected data. Recall, n<30. The result, t = 1.51 shows relationship between CSR, organisational support and employee engagement. The paper recommends that organisations should review their CSR policy bi-annually in accordance with best international standard practice on how to promote relationship between stakeholders and to adopt best strategy on how to reduce menace – environmental pollution caused by activities of corporation on immediate employees and society at large